Computerized Tomographic Scanning in Cases of Dementia - Dietch, James T. (1983)
In assessing the clinical value of computerized tomographic (CT) scanning in elderly patients with dementia, only one of 100 patients with dementia of insidious onset and no other abnormal neurologic signs was found to have a potentially treatable disorder. In a second group of 100 patients with dementia of abrupt onset or with additional abnormal neurologic signs, 12 were found to have a lesion that potentially required medical or surgical intervention. We conclude that a subgroup of patients with dementia, representing about a third of demented patients in our hospital, are unlikely to benefit from CT scanning.